Pemahaman Pelaku Usaha dalam Mengurus Sertifikasi Halal Usaha Mikro Kecil dan Menengah (UMKM) - Junaidi, Junaidi; Afrizal, Jhon; Sukanti, Nadia Deby (STAI Auliaurrasyidin Tembilahan, 2023)
Human need nutrition. The need for nutritien as food is fundamental. Food includes all the basic needs that the body absorbs, such as water, medicines and other substances for body health. On he health side, food not only functions as a source of energy in the body, but can also spread disease. So it is necessery to do food sanitation to avoid disease. On this basis, an understanding of food health as well as halal and good food needs to be dissimenated by government agencies throuth the ministry of relegion, particularly regarding halal certification. This is the basis of the researc carried out, how is the understanding of bussines actors in managing the steps for halal certification for UMKM. This reseach methode is descriptive qualitative with the type of field research. The research was conducted in Indragiri Hilir Regency, Riau. The result of this study show that the understanding the halal certification is quite good, but the socializatin needs to be improved so that knowledge about halal product is even better. One of the organization that can carry out this sosialization is Non-PNS Islamic Religious Extension.